Prebiotic Properties of Dates and Their Impact on Health - Ahmad Alhomsi; Mukaddes Kılıç Bayraktar (Turkish Journal of Agriculture: Food Science and Technology)
The date palm (Phoenix dactylifera L.), primarily cultivated in desert regions like the Middle East, is a significant source of nutrition, rich in sugars, polysaccharides, and bioactive compounds such as carotenoids, flavonoids, phenolics, anthocyanins, and sterols. Notably, the polysaccharides in dates exhibit prebiotic properties, supporting beneficial gut microbiota. Research highlights that dates promote the growth of helpful bacteria, including Bifidobacterium and Lactobacillus, which enhance intestinal health, improve barrier function, and increase the production of short-chain fatty acids. Beyond gut health, dates offer additional benefits, including anti-inflammatory, antioxidant, cardiovascular, neuroprotective, and blood sugar-regulating effects. This review synthesizes recent findings on the prebiotic effects and broader health impacts of dates, suggesting their potential in dietary strategies for promoting health and preventing gastrointestinal disorders.